The effects of corporate governance practices towards shareholders return in Malaysian listed financial sector / Syaizatul Shafiqah Pg Johari - Pg Johari, Syaizatul Shafiqah (2017)
This research project is to examine whether the corporate governance practices with control variables gives an impact towards the shareholders' return of financial sector in Malaysia. The good corporate governance practices involves in balancing the interest of the shareholders, management, and community by which a governance is defined as a process to make decision making and the process by which the decision are implemented and therefore contribute to the earnings of companies as well as the economy of Malaysia, whereas the CEO duality, firm size, growth and profitability are as the control variables in this study. The data sample was collected from the listed financial institutions in Bursa Malaysia and annual reports and it comprises of 21 selected companies in financial sectors based on yearly basis from period of 2012 to 2016. In this study, panel data analysis is used and the findings show that only Growth was found to be positive and significant in influencing the Dividend Payout Ratio. The Non-Executive Directors was found to be positively insignificant towards Dividend Payout Ratio. At the same time, the impact of Board Size, Firm Size and Profitability are deemed to be negatively insignificant towards the Dividend Payout Ratio. This study supports that Corporate Governance is relevant in determining the Shareholders' Return for listed financial institutions in Bursa Malaysia.